2008
DOI: 10.2174/138161208783413239
|View full text |Cite
|
Sign up to set email alerts
|

Xeno-Cannibalism as an Exacerbation of Self-Cannibalism: A Possible Fruitful Survival Strategy for Cancer Cells

Abstract: The term self-cannibalism, or autophagy, was coined to describe the ability of the cells to cannibalize their own damaged organelles or proteins. It was morphologically described as the presence of double-membraned autophagic vesicles filled with diverse cellular materials or debris inside the cells. Hence, more recently, the presence of autophagic vacuoles has been associated with cell survival, including cell senescence and cancer and appears to be activated by nutrient deprivation. The occurrence of autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…A similar phenomenon is observed among epithelial cells in human cancer (Brouwer et al, 1984; Overholtzer et al, 2007; Overholtzer and Brugge, 2008; Sharma and Dey, 2011; Yang and Li, 2012; Cano et al, 2012), suggesting this primeval process may promote survival within the tumour microenvironment (Fais, 2007; Matarrese et al, 2008; He et al, 2013; Lozupone and Fais, 2015). Homotypic epithelial cell cannibalism can occur by entosis, an intriguing process through which one live and viable cell is completely engulfed by another, yielding a ‘cell-in-cell’ structure (Overholtzer et al, 2007).…”
Section: Introductionsupporting
confidence: 68%
“…A similar phenomenon is observed among epithelial cells in human cancer (Brouwer et al, 1984; Overholtzer et al, 2007; Overholtzer and Brugge, 2008; Sharma and Dey, 2011; Yang and Li, 2012; Cano et al, 2012), suggesting this primeval process may promote survival within the tumour microenvironment (Fais, 2007; Matarrese et al, 2008; He et al, 2013; Lozupone and Fais, 2015). Homotypic epithelial cell cannibalism can occur by entosis, an intriguing process through which one live and viable cell is completely engulfed by another, yielding a ‘cell-in-cell’ structure (Overholtzer et al, 2007).…”
Section: Introductionsupporting
confidence: 68%
“…1.6; Gundemir and Johnson, 2009; Lorand and Graham, 2003; Malorni et al, 2008; Park et al, 2010; Zemskov et al, 2006). In this section, we overview and discuss compartment-specific enzymatic and nonenzymatic functions of TG2.…”
Section: Tg2 In Diverse Cellular Compartmentsmentioning
confidence: 99%
“…We abstain from in-depth discussion of various mechanistic aspects of transamidating and GTPase functions of TG2, as excellent reviews on these topics are published elsewhere (Bergamini, 2007; Facchiano and Facchiano, 2009; Kiraly et al, 2011; Mhaouty-Kodja, 2004, Siegel and Khosla, 2007). Likewise, we do not extensively discuss the involvement of TG2 in human disease states, as recent comprehensive reviews in this field either elaborate on the numerous pathophysiological aspects of TG2 function (Iismaa et al, 2009) or focus on its role in inflammation (Elli et al, 2009; Iismaa et al, 2009; Kim, 2006), wound healing and tissue fibrosis (Collighan and Griffin, 2009; Verderio et al, 2004), autoimmunity (Briani et al, 2008; Sollid, 2000), cardiovascular diseases (Bakker et al, 2008; Sane et al, 2007), cancer (Chhabra et al, 2009; Mehta et al, 2010), and neurodegeneration (Bailey et al, 2005; Jeitner et al, 2009; Malorni et al, 2008; Mastroberardino and Piacentini, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…A few studies[1012] in the past have described the feature of xeno-cannibalism, which is phagocytosis of non-self cells and a study has shown that the non-self cell most often phagocytosed is a leukocyte. In 2008, Malorni et al .,[10] explained xeno-cannibalism as an exacerbation of self-cannibalism and a possible fruitful survival strategy for cancer cells.…”
Section: Discussionmentioning
confidence: 99%